Evaluation of Compressive Strength for Recycled Aggregate Concrete Reinforced with Polypropylene Fibers - Omar, Turk (2021)
The compressive strength of recycled aggregate concrete reinforced with polypropylene fibers was investigated. The possibility of using polypropylene fibers (PPF) in the recycled aggregate concrete (RCA) was extensively studied. Moreover, the mixes experimented were using different RCA replacement ratios and different PPF content. The results present the compressive strength behavior of Recycled Aggregate Concrete (RAC) with and without addition of Polypropylene (PP) fibers. The normal coarse aggregate was replaced by recycle aggregate in the percentage of 0, 25, and 50%. The polypropylene fibers (PP) were used in the recycle aggregate concrete by 0.2% and 0.35% by volume. The values of compressive strength of the natural aggregates concrete (NAC) were set as a control. 27 concrete cubes (150x150x150mm) for each RAC and NAC were casted making a total of 54 concrete cubes. Three cubes for each designed mix were also cured for 7 days and 28 days. The test results revealed that the incorporation of PP fibers did not considerably change the compressive strength and the density of concrete, but the compressive strength of RAC was satisfactory at the early ages until the later ages where NAC was higher than RAC. Therefore, use of recycled aggregate concrete showed tolerable performance with respect to compressive strength and will have a better employment at fast setting concrete where early strength is required. Furthermore, more studies are necessary to determine the effect on durability and enhancement to the workability.